Taxonomy, phylogeny and biogeography of seed-harvesting ants in the Tetramorium solidum-group (Hymenoptera: Formicidae) - Mbanyana, Nokuthula (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.